René Petráš (ed.): Aktuální problémy právního postavení menšin v České republice. [Current Problems of the Legal Status of Minorities in the Czech Republic.] Collection of papers from the seminar on Minorities and the Law in the Czech Republic, Prague.: Prague/Office of the Government of the Czech Republic, 2010, 121 pp. - Soukupová, Blanka (Lidé města, 2011)
A review of the book by René Petráš.